Total hip arthroplasty and Paget’s disease: case report and literature review - Cardile, Carlo; Cazzaniga, Carlo; Mosca, Angelo; Ragni, Paolo (Acta Biomedica Atenei Parmensis, 2022)
Paget’s disease (PDB) is a chronic osteopathy more common in male, Caucasic, European population, after the age of 50 years, that can lead to bone deformities. A challenging surgical solution for affected hip with severe hip osteoarthritis is total hip replacement (THA). We describe a case of THA in a 71-year-old patient with PDB and we present a literature review. In particular we find out that more studies comparing cementless THA with cemented one are necessary, in order to understand if one implant is better than the other.